Das formas concretas à lógica do conceito: o papel da teoria do silogismo na ciência da lógica de Hegel - Zoz, Maglaine Priscila (2015)
It is not uncommon when it comes to logical thinking in Aristotelian logic and all the tradition that was accomplished later, which is considered a completed science, and that any increase seems to him unnecessary. What this paper seeks to show is a different way and possible to think about the logic, without that get stuck in a purely formal and closed construction. For this task, the prospect that Hegel gives this science will be set. Hegel's Logic has ramifications that differs from that had been conceived since Aristotle by "logic", because it is not a purely subjective logic, but whose actual truth was laid in autodeterminadora union at the same time subject and object, which can be understood as giving life to the logical processes. It is north of this research and move through their developments, comparing and analyzing in parallel some earlier approaches of logic (as in Aristotle, Kant and Fichte). We will try to expose the development of objective logic, explained in the first and second of the Science of Logic Hegel books. This is to show that reality is thought of as developed in thinking concept as unification of opposites. For this, the course has to be designed as a movement of thought, as a junction of being and thinking, of object and subject, the form and content, and presents this union the element that gives life to the course, because this is the movement in which it carries out the true concept. It is in this context that the syllogism is entered as mediates element whose function sometimes goes unnoticed, but it plays a significant role in the set. The syllogism gives the link that had been missing when it was thought the reconciliation of opposing elements, which ended up turning them into irreconcilable opposites.